Aqueous polyimide containing imidazole diamine and dianhydride monomer copolymer, and preparation method and application thereof
By using water-based polyimide containing imidazole diamine and dianhydride monomer copolymer as a binder on the anode material of lithium-ion batteries, the problems of electrical contact loss and cycle performance decline caused by volume changes of silicon anode are solved, and high thermal stability, mechanical strength and bonding performance are improved, and environmentally friendly water-based synthesis method is adopted.
Patent Information
- Application Number
- CN202411705791.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
AI Technical Summary
The volume of the existing lithium-ion battery anode material silicon changes greatly during the lithiation process, resulting in material breakage, loss of electrical contact and degradation of cycling performance. The commonly used polymer adhesives have unstable chemical properties in extreme environments.
The aqueous polyimide containing imidazole diamine and dianhydride monomer copolymer is used as the binder, and imidazole groups are introduced by copolymerizing APBIA monomers to improve the ionic conductivity and adhesion of the polyimide, and the dependence on organic solvents is reduced through water-based synthesis method.
The thermal stability, mechanical strength and bonding properties of polyimide are improved, the circulation capacity and stability of the negative electrode sheet of lithium-ion battery are enhanced, and an environmentally friendly water-based synthesis method is used.
Smart Images

Figure CN119570026A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a water-based polyimide containing a copolymer of imidazole diamine and dianhydride monomers, a preparation method and application thereof. Background Art
[0002] The burning of fossil fuels to power cars, generate electricity, and run factories has been identified as a major cause of global warming. To reduce the rate at which fossil fuels are burned, it is necessary to produce energy-efficient devices such as electric vehicles, but such products rely on systems that can store large amounts of energy, so there is an increasing demand for lithium-ion batteries (LIBs) with increasing energy density [Nat. Mater., 2010, 9, 353–358.]. To date, a variety of negative electrode materials have been studied to increase the energy density of LIBs, such as hard / soft carbon including graphene, lithium alloys (Si, Sn, Al, Sb, etc.), transition metal oxides (CoO, Co3O4, MnO2, MoO3, TiO2, etc.), and chromium compounds. Among them, silicon-based anodes have a very high theoretical capacity (4200 mAh g -1 , Li 4.4 Si), low cost, benign impact on the environment and natural abundant resources are considered to be the most promising alternative to lithium battery anodes.
[0003] Silicon has an extremely high theoretical energy density (4200 mAh g -1 ), low reduction potential (0.2 V vs Li / Li + ), and at a low cost. Therefore, the use of silicon in lithium-ion batteries appears to be an attractive way to increase battery energy density and produce high-performance batteries. Silicon active materials undergo an alloying / alloying process (4.4Li + +4.4e - + Si ↔Li 4.4 Si has a theoretical capacity of about 10 times that of graphite [Adv. Mater. 2013, 25, 1571–1576.]. However, silicon-based electrodes undergo a volume change of up to 300% during lithiation (alloying), which may cause the silicon active material to break and fall off the copper current collector, resulting in loss of electrical contact, increased internal resistance and loss of active materials, which seriously reduces the cycle performance [Chem. Soc. Rev. 2018, 47, 2145–2164].
[0004] Considering efficient large-scale production and cost competitiveness, the use of highly functional polymer binder materials is considered to be the most effective way to alleviate the volume change of silicon anodes and improve the electrochemical performance of silicon anodes. Therefore, polymer binders with excellent mechanical strength have been developed, which can withstand large volume changes through van der Waals forces, supramolecular interactions (such as hydrogen bonds, ion-dipole interactions) or cross-linking bonds. However, most of the developed binders are linear polymers, such as polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMCNa), etc., which have the disadvantages of poor thermal stability and unstable chemical properties in extreme environments [Nano Energy 2015, 12, 178–185.].
[0005] Polyimides (PIs) are a special engineering material with good mechanical properties, chemical resistance, thermal stability and moisture resistance. They have been shown to be useful as binders for silicon anodes [Eur. Polym. J. 2002, 38, 815–828.]. However, the synthesis and polymerization of polyimides require the use of highly polar organic solvents such as dimethylacetamide (DMAC), dimethylformamide (DMF) and N-methyl-2-pyrrolidone (NMP). Since these organic solvents are harmful to the environment and expensive, their use in industry has been strictly restricted in recent years [Polym. Degrad. Stab. 2011, 96, 2174–2180.].
[0006] In order to overcome this shortcoming, the present invention uses a water-based synthesis method to first synthesize water-soluble polyamic acid salts. According to literature reports (ACS Appl. Mater. Interfaces 2015, 7, 23545−23553), imidazole groups have both donor hydrogen bonding sites and acceptor hydrogen bonding sites, which can not only form ionic interactions with polar groups, but also coordinate with lithium ions, and have excellent thermal stability. Therefore, the present invention uses 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) monomers, and introduces imidazole groups into the polyimide skeleton by copolymerizing APBIA, which will improve the problems of poor ion conductivity and insufficient adhesion of polyimide. Summary of the invention
[0007] The purpose of the present invention is to provide a water-based polyimide based on a copolymer of imidazole diamine and dianhydride monomers, which has high thermal stability, excellent mechanical properties and excellent bonding properties, a preparation method and application thereof.
[0008] The present invention provides a copolymer containing imidazole diamine and dianhydride monomers, the main chain of which is composed of a high molecular weight rigid aromatic skeleton and combined with amphoteric imidazole groups. It is copolymerized with highly reactive monomer p-phenylenediamine to obtain a high molecular weight polymer, which has both the polarity of the imidazole group and lithium ion affinity. The obtained copolymer of imidazole diamine and dianhydride monomers has excellent chemical stability, film-forming properties, electrical conductivity and mechanical strength. To achieve the above purpose, the technical solution adopted by the present invention is:
[0009] A precursor of an aqueous polyimide (APBIA-PI) containing a copolymer of an imidazole diamine and a dianhydride monomer, which is generated by reacting raw materials of a dianhydride component and a diamine component, and comprises a copolymer of the following repeating structural units:
[0010]
[0011] Wherein, x+y=1, 0≤x≤1, 0≤y≤1; for example, x is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1. For example, y is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1.
[0012] A represents at least one of the following groups: a tetravalent organic group of an aromatic tetracarboxylic acid that does not contain fluorine, but does not contain a carboxyl group; a tetravalent organic group of an aliphatic tetracarboxylic acid that does not contain a carboxyl group; for example, A is a residue derived from a dianhydride monomer, and A is at least one of the following groups:
[0013]
[0014] B represents at least one of the following groups: a divalent organic group of an aromatic diamine that does not contain fluorine, whose solubility in water is greater than 0.1 g / L (25°C) and does not contain an amino group; a divalent organic group of an aliphatic diamine, whose relative molecular mass does not exceed 500 and does not contain an amino group; for example, B is a residue derived from a diamine monomer, and B is at least one of the following structures:
[0015]
[0016] M is an imidazole organic compound, which reacts with the carboxyl group of polyamic acid to form a water-soluble polyamic acid salt, and its characteristics are as follows:
[0017]
[0018] Wherein, X1 to X4 represent a hydrogen atom or an alkane group having less than 5 carbon atoms.
[0019] The method for preparing an aqueous polyimide containing a copolymer of imidazole diamine and dianhydride monomers of the present invention comprises the following steps:
[0020] (1) At room temperature, firstly, one or more of APBIA and diamine monomers containing a B group are dissolved in deionized water, then at least one of imidazole organic compounds M is added to the solution and stirred for at least 1 hour to prepare a transparent solution, and then a dianhydride monomer containing an A group is added and dissolved in the aforementioned solution, wherein the molar ratio of the dianhydride monomer containing an A group to the diamine monomer containing a B group is 0.89-1.35:1 (for example, the molar ratio of the dianhydride monomer to the diamine monomer containing a B group is 0.89-1.35:1). The molar ratio of the diamine monomer is 0.89:1, 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.99:1, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.05:1, 1.07:1, 1.09:1, 1:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1, 1.3:1 or 1.35:1), and the solution concentration is controlled at 10-30wt%. %, the molar ratio of the imidazole organic compound M to the dianhydride monomer containing the A group is greater than 2.0 (for example, the molar ratio of the imidazole organic compound M to the dianhydride monomer containing the A group is 2, 2.5, 2.6, 2.8, 3, 3.2, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10);
[0021] (2) Under an inert gas environment, react the mixture in (1) for at least 6 hours to obtain an aqueous polyimide precursor solution having a certain viscosity.
[0022] The aqueous polyimide precursor solution containing the copolymer of imidazole and dianhydride monomers obtained by the invention is used as an electrode binder in lithium ion batteries.
[0023] 1) Steps for manufacturing electrodes: Dissolve the negative electrode active material (including but not limited to silicon, graphite or silicon-carbon composite materials, etc.), conductive agent, and polyimide precursor solution in deionized water in a certain proportion, and mix them evenly using magnetic stirring and ultrasonic waves. Use a coating preparation device to evenly coat the slurry on one side of the current collector. Here, the solid content of the polyimide precursor solution is greater than 1wt%, and the loading amount of the negative electrode active material is not less than 0.2 mg·cm -2 ;
[0024] 2) drying the coated electrode in a forced air oven at 60°C for 0.1-3h, and then transferring the electrode to a vacuum oven for treatment at a higher temperature (>120°C) for 0.1-12h to complete the imidization process of the polyimide precursor;
[0025] 3) The current collector after solvent drying is made into a circular electrode sheet with a diameter of 10-14 mm on a manual slicer. The mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating;
[0026] 4) Complete the installation of the lithium-ion battery buckle.
[0027] The aqueous polyimide precursor solution containing the copolymer of imidazole and dianhydride monomers obtained in the present invention is used as a method for preparing a polyimide film, comprising the following steps:
[0028] The obtained aqueous polyimide precursor solution containing the copolymer of imidazole and dianhydride monomers is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 60°C-100°C for 1h-24h to form a film, then vacuum dried at 80°C-120°C for 0.5h-24h, and vacuum treated at 150°C-350°C for 0.5h-12h to complete the imidization process and obtain a polyimide film.
[0029] The beneficial results of the present invention are:
[0030] (1) The present invention discloses a copolymer containing imidazole diamine and dianhydride monomers with mild polymerization conditions and harmless solvents. It can be used to prepare polyimide with excellent organic solvent resistance and polar imidazole groups on the main chain;
[0031] (2) An aqueous polyimide precursor solution containing a copolymer of an imidazole diamine and a dianhydride monomer is used as a negative electrode binder for a lithium ion battery to prepare a negative electrode sheet having good bonding properties and good electrolyte tolerance.
[0032] (3) The polyimide prepared from the copolymer of imidazole diamine and dianhydride monomer has good thermal stability, and the polymer decomposition temperature can reach 300-500℃;
[0033] (4) The negative electrode sheet prepared in the above (2) is applied to a lithium-ion battery, and the obtained battery has excellent cycle capacity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the cycling performance curve of the silicon electrode prepared in Example 1 in a lithium-ion battery test device at room temperature.
[0035] Figure 2 This is the peeling force curve of the silicon electrode sheet prepared in Example 1. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is described in detail below through specific examples, but it should be clearly stated that these examples are used for illustration and are not to be construed as limiting the scope of the present invention.
[0037] Example 1:
[0038] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, first dissolve p-phenylenediamine (PPD) monomer (9.73 g, 0.09 mol) and 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) (2.2 g, 0.01 mol) in deionized water, then add an equivalent amount of 1,2-dimethylimidazole (DMIZ) (24.03 g, 0.25 mol) and mechanically stir at 25 ° C for 1 h to prepare a transparent solution. Then add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) monomer (29.42 g, 0.1 mol) and dissolve it in the above solution. Mechanically stir at 70 ° C for 6 h. The concentration of dianhydride and diamine monomers in the solution is controlled at 15 wt%;
[0039] (2) The obtained aqueous polyimide precursor solution is directly cast on a glass plate or a stainless steel plate, flattened with a film casting knife, and cast into a film at room temperature. The film is treated at 60°C for 1 hour, and then vacuum treated at 120°C for 1 hour. The imidization process is completed at 250°C for 1 hour to obtain a polyimide film (60±5 um).
[0040] (3) Table 1 summarizes the properties of aqueous polyimide precursor solutions and polyimides.
[0041] The application of the aqueous polyimide precursor solution of the present invention comprises the following steps:
[0042] The obtained aqueous polyimide precursor solution is used in a lithium ion battery device.
[0043] 1) Prepare the silicon anode of the lithium-ion battery. The anode is prepared as follows: mix the aqueous polyimide precursor solution with deionized water, conductive carbon black (TIMCAL, Super C45), and nanosilicon (Canrd, 80-100nm) in a mass ratio of 10:10:80, and stir magnetically for 12-24 hours. After ultrasonic treatment for 30 minutes, apply the obtained slurry on the copper foil with a scraper (the coating thickness is 100um). Dry the prepared electrode at 60°C for 1 hour, and then vacuum treat it at 150°C for 6 hours to obtain a silicon negative electrode sheet;
[0044] 2) The current collector after solvent drying was made into a circular electrode sheet with a diameter of 12 mm on a manual slicer. The mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating; the loading amount of active material was controlled at 1.2 mg / cm 2;
[0045] 3) All battery assemblies were carried out in an argon atmosphere glove box, and the water and oxygen content in the glove box was less than 0.1ppm. The prepared electrode sheet was used as the working electrode, the metal lithium sheet was used as the negative electrode, and a mixture containing 1.0 M / L lithium hexafluorophosphate (LiPF6), 1:1 volume ratio of ethylene carbonate (EC) and diethyl carbonate (DEC) and 10% volume ratio of fluoroethylene carbonate (FEC) additive was used as the electrolyte. Figure 1 After the packaged button cell is left to stand for 12 hours, the cycle performance test can be carried out: after 2 cycles of activation at 1.0A / g, the test starts at 4.2A / g and the temperature is 25°C.
[0046] Figure 1 For Example 1, a binder was prepared for application in a cycling performance curve of a silicon-based half-cell. The test was conducted at 25°C. After 2 cycles of charge and discharge at 1.0 A / g, the battery was charged and discharged for 100 cycles at a high current density of 4.2 A / g. Even at a high current density of 4.2 A / g, the battery still had excellent cycling capacity and stability: after 100 cycles of charge and discharge, the battery still had a high capacity of 2432 mAh / g and a capacity retention rate of 68.0%.
[0047] Figure 2 The 180° peeling curve of the electrode piece is prepared for Example 1. The specific test method is to prepare the electrode piece into 80mm For a 20mm sample, fix the 3M tape on the steel plate, and fix the copper foil side of the sample on the 3M tape (Canrd, pole piece adhesion test tape); and use another 3M tape to stick the adhesive layer of the sample. Use a universal tensile testing machine to perform a 180° peel test. The test results show that the adhesive prepared in Example 2 has excellent bonding performance, and the peel force is as high as 20N, proving that after the introduction of imidazole diamine, polyimide still has excellent bonding properties.
[0048] Example 2:
[0049] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly dissolve PPD (8.65g, 0.08mol) and APBIA (4.48g, 0.02mol) in deionized water, then DMIZ (24.03g, 0.25 mol), and mechanically stir for 1h at 25℃ to prepare a transparent solution. Then add BPDA monomer (29.42g, 0.1mol), and also dissolve it in the above solution, and mechanically stir for 6h at 70℃, and the concentration of dianhydride and diamine monomer in the solution is controlled at 15 wt%; the rest of the experimental steps and application steps are the same as Example 1.
[0050] Example 3:
[0051] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, first dissolve p-PPD (6.49g, 0.06mol) and APBIA (0.04mol) in deionized water, then add DMIZ (24.03g, 0.25mol) and stir mechanically at 25℃ for 1h to prepare a transparent solution. Then add BPDA monomer (29.42g, 0.1mol), also dissolved in the above solution, stir mechanically at 70℃ for 6h, and the concentration of dianhydride and diamine monomer in the solution is controlled at 15 wt%; the rest of the experimental steps and application steps are the same as Example 1.
[0052] Example 4:
[0053] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PPD (8.65g, 0.08mol) and APBIA (4.48g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, 4,4'-oxydiphthalic anhydride (ODPA) monomer (31.02g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 60℃ for 6h. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0054] Example 5:
[0055] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PPD (8.65g, 0.08mol) and APBIA (4.48g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) monomer (32.22g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 6h. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0056] Example 6:
[0057] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PPD (8.65g, 0.08mol) and APBIA (4.48g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, 3,3,4,4-diphenylsulfone tetracarboxylic dianhydride (DSDA) monomer (35.82g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 6h. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0058] Example 7:
[0059] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PPD (8.65g, 0.08mol) and APBIA (4.48g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, 2,3,3',4'-biphenyltetracarboxylic dianhydride (α-BPDA) monomer (29.42g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 6h. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0060] Example 8:
[0061] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PPD (8.65g, 0.08mol) and APBIA (4.48g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, cyclobutanetetracarboxylic dianhydride (CBDA) monomer (19.61g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 6h. The concentration of dianhydride and diamine monomer in the solution was controlled at 15 wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0062] Example 9:
[0063] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, first dissolve m-phenylenediamine (MPD) (8.65g, 0.08mol) and APBIA (4.48g, 0.02mol) in deionized water, then add DMIZ (24.03g, 0.25mol) and mechanically stir for 1h at 25℃ to prepare a transparent solution. Then add BPDA monomer (29.42g, 0.1mol) and dissolve it in the above solution. The concentration of dianhydride and diamine monomer in the solution is controlled at 15 wt%; the rest of the experimental steps and application steps are the same as Example 1.
[0064] Example 10:
[0065] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, PPD (8.65g, 0.08mol), 3,5-diaminobenzoic acid (DABA) monomer (1.52g, 0.01mol) and APBIA (2.24g, 0.01mol) were first dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was mechanically stirred at 25°C for 1h to prepare a transparent solution. Then BPDA monomer (29.42g, 0.1mol) was added and dissolved in the above solution. The concentration of dianhydride and diamine monomers in the solution was controlled at 15wt%; the rest of the experimental steps and application steps were the same as in Example 1.
[0066] Example 11:
[0067] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, PPD (8.65g, 0.08mol), 2,4-diaminotoluene (2,4-TDA) (1.22g, 0.01mol) and APBIA (2.24g, 0.01mol) were first dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then BPDA monomer (29.42g, 0.1mol) was added and dissolved in the above solution. The concentration of dianhydride and diamine monomer in the solution was controlled at 15 wt%; the rest of the experimental steps and application steps were the same as in Example 1.
[0068] Example 12:
[0069] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, PPD (8.65g, 0.08mol), 3,3'-diaminodiphenyl sulfone (AS33) monomer (2.48g, 0.01mol) and APBIA (2.24g, 0.01mol) were first dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then BPDA monomer (29.42g, 0.1mol) was added and dissolved in the above solution. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the rest of the experimental steps and application steps were the same as Example 1.
[0070] Example 13:
[0071] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, PPD (8.65g, 0.08mol), 6,6'-diamino-3,3'-methylenedibenzoic acid (MBAA) (2.86g, 0.01mol) and APBIA (2.24g, 0.01mol) were first dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then BPDA monomer (29.42g, 0.1mol) was added and dissolved in the above solution. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the remaining experimental steps and application steps were the same as Example 1.
[0072] Example 14:
[0073] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, PPD (8.65g, 0.08mol), benzidine disulfonic acid (BDSA monomer) (3.44g, 0.01mol) and APBIA (2.24g, 0.01mol) were first dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then BPDA monomer (29.42g, 0.1mol) was added and dissolved in the above solution, and mechanically stirred at 70℃ for 6h. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the rest of the experimental steps and application steps were the same as in Example 1.
[0074] Example 15:
[0075] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, 4,4'-diaminodiphenyl ether (ODA) monomer (16.02g, 0.08mol) and APBIA (4.48g, 0.02mol) were first dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then BPDA monomer (29.42g, 0.1mol) was added and dissolved in the above solution, and mechanically stirred at 70℃ for 6h. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the rest of the experimental steps and application steps were the same as in Example 1.
[0076] Example 16:
[0077] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, 1,6-hexanediamine (HMDA) (9.30g, 0.08mol) and APBIA (4.48g, 0.02mol) were first dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was mechanically stirred at 25°C for 1h to prepare a transparent solution. Then BPDA monomer (29.42g, 0.1mol) was added and dissolved in the above solution, and mechanically stirred at 70°C for 6h. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the remaining experimental steps and application steps were the same as Example 1.
[0078] Comparative Example 1:
[0079] In this example, a polyimide precursor solution without APBIA during copolymerization was used as a comparative example: in an inert gas environment, PPD (10.81 g, 0.1 mol) was first dissolved in deionized water, and then DMIZ (24.03 g, 0.25 mol) was added, and mechanically stirred for 1 h at 25°C to prepare a transparent solution. Then BPDA (29.42 g) monomer was added and dissolved in the aforementioned solution, and mechanically stirred for 6 h at 70°C. The concentration of dianhydride and diamine monomers in the solution was controlled at 15 wt%; the remaining experimental steps and application steps were the same as those in Example 1.
[0080] Comparative Example 2:
[0081] This example uses commercial polyacrylic acid (Aladdin, Mw=450000) as a comparative example, and its application steps are the same as those of Example 1.
[0082] Comparative Example 3:
[0083] This example uses commercially available sodium carboxymethyl cellulose (DAICEL, CMC-2200) as a comparative example, and its application steps are the same as those of Example 1.
[0084] Table 1
[0085]
[0086] Table 1 Test method for data
[0087] Intrinsic viscosity dL g-1 test method: prepare the test sample into a 5 mg / L solution, use an Ubbelohde viscometer to measure the solvent retention time t0 / s and the test sample retention time t / s, and calculate the intrinsic viscosity according to the following formula:
[0088] ,
[0089] Rotational viscosity Pa s test method: Tested using a rheometer at 50°C;
[0090] Test method for glass transition temperature ℃: Prepare polyacrylic acid / polyimide composite film into 40mm The 8mm sample was loaded on a dynamic thermomechanical analyzer, and the measurement temperature range was 50-350°C, with a heating rate of 5°C / min. The glass transition temperature was obtained based on the changes in the storage modulus and loss modulus.
[0091] Elastic modulus Gpa Elastic strength Mpa Elongation at break % Test method: Prepare polyacrylic acid / polyimide composite film into 60mm The sample was 10 mm thick and loaded on a universal tensile testing machine with a tensile rate of 50 mm / min.
[0092] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A water-based polyimide (APBIA-PI) containing a copolymer of imidazole diamine and dianhydride monomers, which is produced by reacting raw materials containing a dianhydride component and a diamine component, characterized in that: A copolymer comprising the following repeating structural units: , Among them, x+y=1, 0≤x≤1, 0≤y≤1; A is selected from at least one of the following groups: a tetravalent organic group of an aromatic tetracarboxylic acid that does not contain fluorine, but does not contain a carboxyl group; a tetravalent organic group of an aliphatic tetracarboxylic acid that does not contain a carboxyl group; for example, A is at least one of the following groups: , B represents at least one of the following groups: a divalent organic group of an aromatic diamine that does not contain fluorine and does not contain an amino group; a divalent organic group of an aliphatic diamine whose relative molecular mass does not exceed 500 and does not contain an amino group; for example, B is at least one of the following groups: , The structural formula of M is as follows: , Wherein, X1 to X4 represent a hydrogen atom or an alkane group having less than 5 carbon atoms.
2. The method for preparing the polyimide according to claim 1, characterized in that: The steps include: (1) First, at room temperature, 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and one or more of the diamine monomers containing a B group are dissolved in deionized water, then at least one of the imidazole organic compounds M is added to the solution, and stirred for at least 1 hour to prepare a transparent solution, and then a dianhydride monomer containing an A group is added and dissolved in the aforementioned solution, wherein the molar ratio of the dianhydride monomer containing an A group to the diamine monomer containing a B group is 0.89-1.35:1, the solution concentration is controlled at 10-30wt%, and the molar ratio of the imidazole organic compound M to the dianhydride monomer containing an A group is greater than 2.0; (2) Under an inert gas environment, react the mixture in (1) for at least 6 hours to obtain an aqueous polyimide precursor solution.
3. The use of the polyimide prepared by the method according to claim 2, characterized in that: As an electrode binder, it is used in lithium-ion batteries, comprising the following steps: 1) Steps for manufacturing electrodes: dissolving negative electrode active materials (including but not limited to silicon, graphite or silicon-carbon composite materials, etc.), conductive agents, and polyimide precursor solutions in deionized water, and mixing them evenly using magnetic stirring and ultrasonic waves; using a coating preparation device to evenly coat the slurry on one side of the current collector; here, the solid content of the polyimide precursor solution is greater than 1wt%, and the loading amount of the negative electrode active material is not less than 0.2 mg·cm -2 ; 2) The coated electrode is placed in a forced air oven at 60-80°C for 1-3 hours and then transferred to a vacuum oven for treatment at a higher temperature (>120°C) for 2-12 hours to complete the imidization process of the polyimide precursor; 3) The current collector after solvent drying is made into a circular electrode sheet with a diameter of 10-14 mm on a manual slicer; the mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating; 4) Complete the installation of the lithium-ion battery buckle.
4. The use of the polyimide prepared by the method according to claim 2, characterized in that: The steps include: The obtained aqueous polyimide precursor solution is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 60-100°C for 5-24h to form a film, then vacuum dried at 80-120°C for 5-24h, and vacuum treated at 150°C-350°C for 1-12h to complete the imidization process and obtain a polyimide film.